Analyzing the Convenience and Challenges of Transitioning from Physical to Digital Wallets: A Case Study of QRIS Adoption in Small Businesses - Fauziah Ayu; Zidni Ma'ruf; Indra Sugiarto; Muhammad Bimo Alrizky; Muhammad Restu Ardyan (Jurnal Inovasi Bisnis dan Kewirausahaan, 2026)
The switch from payments to digital payment systems is really important in Indonesia especially with the introduction of Quick Response Code Indonesian Standard also known as QRIS. This study is about looking at how easy or hard it's for small businesses to use QRIS as a way to pay digitally. We used a method to gather information, where we talked to five small business owners in South Sumatra who already use QRIS in their daily work. We found out that QRIS has a lot of things like making transactions faster,cashless, and more efficient. Most customers also like using QRIS because it's easy to use and convenient. We think that QRIS is a thing for small businesses, in Indonesia and it can help them a lot. However, The study found some problems with QRIS. For example the internet connection is not always working there are system errors people need to use their smartphones some customers do not know how to use things and there are fees for transactions. These problems show that even though QRIS helps people move to payments there are still some technical and operational issues that make it hard for small businesses to use QRIS. Overall, This study says that QRIS is good for businesses and customers. We need to keep helping people learn about digital things and make the internet work better so that digital payments can really work well in Indonesia. We need to do more to make sure it works properly for small businesses and customers, in Indonesia.